2017
DOI: 10.1063/1.4990077
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of 23S metastable state He atoms in low-temperature recombining plasmas

Abstract: We measured the electron density and temperature using laser Thomson scattering and metastable state (2 3 S) of He atoms using laser absorption spectroscopy in the detached recombining plasmas in the divertor simulator NAGDIS-II. Using the measured electron density and temperature combined with the particle trajectory trace simulation, we discussed the behavior of the metastable state He atoms based on comparisons with the experimental results. It is shown that the metastable states atoms are mainly produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In order to reduce the stray light, baffles are equipped on the laser path, and a viewing dump is placed at the end of the field of view (detailed setup was described in Ref. [5]). Detachment was induced by controlling the neutral gas pressure, P, via the amount of injected gas near the end target.A typical LTS spectrum and fitting curve in attached He plasma (P = 5 mTorr) are shown in Fig.…”
mentioning
confidence: 99%
“…In order to reduce the stray light, baffles are equipped on the laser path, and a viewing dump is placed at the end of the field of view (detailed setup was described in Ref. [5]). Detachment was induced by controlling the neutral gas pressure, P, via the amount of injected gas near the end target.A typical LTS spectrum and fitting curve in attached He plasma (P = 5 mTorr) are shown in Fig.…”
mentioning
confidence: 99%
“…In period II, it is seen that spiral structure was clearly detached from the plasma column. Recently, laser Thomson scattering in NAGDIS-II revealed that a cold (∼0.1 eV) high density plasma existed in the peripheral region in detached plasmas [14]. It is likely that the plasma blowoffs shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An LTS measurement system, installed on the downstream side of the NAGDIS‐II, is able to measure T e below 1 eV. Measured T e by using the LTS was compared with T ed measured with the double probe at the same position.…”
Section: Methodsmentioning
confidence: 99%